Analisis Pengaruh Servicescape Dan Inovasi Layanan Terhadap Kepuasan Masyarakat Dengan Kepercayaan Sebagai Variabel Mediasi (Studi Tentang Pelayanan Pendaftaran Haji di Kota Semarang) - Imam Sucahyo; Grace Tiana Solovida (Magister Manajemen STIE Bank BPD Jateng, 2022)
The benefits of this research are to determine the effect of servicescape and service innovation on community satisfaction and the role of trust in mediating the effect of servicescape and service innovation on community satisfaction. This research was conducted at the Office of the Ministry of Religion in Semarang City. The questionnaire that has been tested for validity and reliability is addressed to 98 respondents. The data collection method uses questionnaires, literature, observation, documentation and interviews. Meanwhile, the measurement of data analysis uses smartpls and determination tests. The measurement results between t-statistical variables show (1) Servicescape has no positive and significant effect on satisfaction (1.95), (2) Servicescape has a positive and significant effect on trust (2.82), (3) Trust has a positive and significant effect on satisfaction (3.53), (4) Trust is able to mediate the effect of servicescape on community satisfaction (2.10), (5) Service innovation has a positive and significant effect on community satisfaction as seen from the t-count value of (3.11), (6 ) Service innovation has a positive and significant effect on trust seen from the t value of (5.03), (7) Trust is able to mediate the effect of service innovation on community satisfaction (2.58).